Pengaruh Desain Arsitektur terhadap Aksesibilitas Lansia: Bangunan Masjid Raya Bandung - Debby Nurterra Achsanta; Aldyfra Luhulima Lukman (Arsir: Jurnal Arsitektur, 2026)
Accessibility for the elderly in public spaces, especially mosques, is very important to create an inclusive and safe environment. The Grand Mosque of Bandung, as one of the main mosques in the city center with very diverse visitors, is an important study to examine the extent to which its architectural design supports the comfort and convenience of the elderly in worship. This mosque also functions as a center for social and cultural activities that are often visited by the elderly as an active community. With the increasing number of elderly people and the need for accessible spaces, this study is important to assess the suitability of the mosque design with accessibility standards. This study uses observations and interviews of the elderly as well as evaluation of architectural elements based on PUPR Ministerial Regulation No. 14/2017 and PP No. 16/2021, focusing on the dimensions of the stairs, the width of the access path, the slope of the ramp, and supporting facilities such as toilets and ablution. The results show that several aspects such as uneven stairs, limited ramps, and less than optimal facilities do not meet accessibility standards. These findings emphasize the need for design improvements to create a more inclusive and comfortable mosque for the elderly, as well as being a recommendation for mosque managers and designers.